2017
DOI: 10.1177/1356336x17732964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of situational interest dimensions on students’ learning strategies in physical education

Abstract: Previous studies have shown that situational interest, as a primary motivator for students, affects student cognitive engagement. Considering this, the purpose of this study was to examine, within a situated perspective, the effects of situational interest dimensions on students’ learning strategies in physical education. A total of 148 tenth-grade students (mean age = 16.1, 15–17 years, standard deviation = 1.3, 40% boys) participated in a 30-minute body-conditioning learning task. Students’ situational inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
1
12
0
10
Order By: Relevance
“…Teachers should support the high level of interest of students to physical culture classes. Scientists confirm that situational interest is the main motivation for students in the field of physical training [42]. It is revealed that positive emotions and increase in popularity among coursemates are the main motives to sports activities and physical activity in students from European countries [22].…”
Section: Discussionmentioning
confidence: 99%
“…Teachers should support the high level of interest of students to physical culture classes. Scientists confirm that situational interest is the main motivation for students in the field of physical training [42]. It is revealed that positive emotions and increase in popularity among coursemates are the main motives to sports activities and physical activity in students from European countries [22].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained as the National Association for Sport and Physical Education (NASPE) survey of 2001 in the US encouraged PE teachers ‘to teach a variety of physical activities that promoted PE classes as fun and enjoyable’ (Roure & Pasco, 2018a: 5). In French PE however, the novelty component had less effect on total interest, as this context is centered more on the teaching of the same physical activities throughout the curriculum in order to promote students’ cognitive development and learning methods (Roure, Kermarrec & Pasco, 2017). Given this, the novelty dimension seems to be related to the uniqueness of students’ SI.…”
Section: Situational Interest In the French And Us Physical Educationmentioning
confidence: 99%
“…In contrast to the Walloon teachers who use an analytical approach for the teaching and learning processes, teachers in the canton of Vaud prioritize their relationships with their students, maintaining a sense of fairness between them (Allain, Deriaz, Voisard & Lentillon-Kaestner, 2015). Nevertheless, these two PE contexts try to enhance students’ levels of enjoyment within the lessons, which differentiate them from the French PE context which is more centered on learning processes and the students’ cognitive development (Roure et al, 2017).…”
Section: The Three French-speaking Contexts Of Pementioning
confidence: 99%
“…Keterlibatan aktivitas fisik dan hasil belajar gerak secara langsung akan dipengaruhi oleh interaksi antara pengetahuan, kesenangan dan strategi pembelajaran. Situational interest dipengaruhi oleh strategi pembelajaran yang disajikan oleh guru saat proses belajar mengajar penjas pada materi bolavoli dan softball, (Kermarrec and Pasco, 2017). Tanpa ada situational interest yang timbul dari dalam diri siswa maka belajar gerak akan terhambat yang berdampak pada tidak tercapainya tujuan pembelajaran penjas.…”
Section: Pendahuluanunclassified
“…Tidak hanya reward, punishment memiliki peranan penting dalam proses pembelajaran penjas, (Steel et al, 2016) (Kermarrec and Pasco, 2017). Situational interest akan tercipta pada saat memulai pembelajaran.…”
Section: Pendahuluanunclassified